MODEL TREATMENT OF EXAMINATION SESSIONS HIGHER EDUCATION INSTITUTIONS MEANS OLAP - Труш, О.; Чабан, Т. (Science-based technologies, 2011)
The article is dedicated to a comparative analysis of the OLAP’s (Online Analytical Processing) usability to store information about the result of university students and analyze data based on objective factors.